2009
DOI: 10.1016/j.pbb.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Progestogens and estrogen influence impulsive burying and avoidant freezing behavior of naturally cycling and ovariectomized rats

Abstract: Steroid hormones, progesterone and estradiol, may influence approach and/or anxiety behavior. Female rats in behavioral estrus, have elevated levels of these steroid hormones and demonstrate more approach and less anxiety behavior than do diestrous rats. Ovariectomy obviates these cyclic variations and systemic progesterone and/or estrogen replacement can enhance approach and anti-anxiety behavior. However, the role of progesterone and/or estrogen in mediating impulsive, avoidant and/or fear behaviors requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Progesterone levels fluctuate across the estrous cycle, undergoing a sharp peak shortly after that of estrogen, at the approximate beginning of the night of PRO (Staley and Scharfman, 2005). When administered either alone or with estradiol, progesterone given before extinction learning facilitates extinction retrieval in intact animals (Milad et al, 2009), and suppresses freezing in ovariectomized rats (Llaneza and Frye, 2009). In addition, there is evidence that progesterone can interact with dopaminergic systems (Frye and Sora, 2010;Yu and Liao, 2000), but how these interactions might influence extinction learning and retrieval has not been tested directly.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone levels fluctuate across the estrous cycle, undergoing a sharp peak shortly after that of estrogen, at the approximate beginning of the night of PRO (Staley and Scharfman, 2005). When administered either alone or with estradiol, progesterone given before extinction learning facilitates extinction retrieval in intact animals (Milad et al, 2009), and suppresses freezing in ovariectomized rats (Llaneza and Frye, 2009). In addition, there is evidence that progesterone can interact with dopaminergic systems (Frye and Sora, 2010;Yu and Liao, 2000), but how these interactions might influence extinction learning and retrieval has not been tested directly.…”
Section: Discussionmentioning
confidence: 99%
“…While tetrahydrofurandiols do not bind ER alpha, it has been shown to inuence ER levels in the brain and alter behavior by an unknown mechanism of action [23,49]. Notably, developmental exposure to estrogens (and progestins) has been shown to inuence anxiety-like behavior in male and female rodents, acting as an anxiolytic [50][51][52][53]. Likewise, through development, intake of phytoestrogens via diet has been shown to decrease anxiety-like behavior in Long-Evans rats in a similar direction as shown in this manuscript [54].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty percent of female rats bury more marbles in dioestrous, in comparison with prooestrous, and this is attenuated by acute treatment with the antidepressants fluoxetine, nomifensine and the anxiolytic diazepam (Schneider and Popik, 2007). Accordingly, female rats spend more time burying in dioestrous than in prooestrous (Llaneza and Frye, 2009). However, others have found that in this test, female rats in prooestrous are more sensitive to diazepam, than male and female rats in dioestrous (Fernandez-Guasti and Picazo, 1990).…”
Section: Sex Differences In Models Of Ocdmentioning
confidence: 99%